1976
DOI: 10.2176/nmc.16pt1.77
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Head Injury & Concussion in Monkey Using Pure Linear Acceleration Impact

Abstract: SummaryTranslational acceleration head injury experiment was performed on 12 Japanese monkeys and one baboon using a HYGE sled and a slider-impactor system. All the monkeys became concussed by force ranging 241 to 366G in slider average acceleration and two of them died of concussion (fatal or irreversible concussion). The fatal concussion animals as well as the delayed death ones showed almost unexceptionally rib and clavicle fractures and mediastinal hemorrhage. Subarachnoid hemorrhage seen in six animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Analyses of data from early nonhuman primate studies of concussion led investigators at the time to believe that approximately half of the potential for concussion during impact to the unprotected movable head was related to head rotation, with the remaining brain injury potential of the blow being related to the contact phenomena of the impact. [86][87][88][89] Although the biodynamics in these primate models were likely more similar to human concussion, such studies were limited to small group size. With regard to modern-day athletes and the biophysics of mTBI, data garnered through helmet accelerometer studies at the youth, high school, and college level have shown that athletes may experience a wide range of head impacts, as well as types of forces, and this research has also suggested that it may be more likely be that the cumulative number of head impacts best correlates with the potential for concussion occurrence or chronic effects.…”
Section: Chronic Behavioral Sequelae After Repetitive Mild Traumatic mentioning
confidence: 99%
“…Analyses of data from early nonhuman primate studies of concussion led investigators at the time to believe that approximately half of the potential for concussion during impact to the unprotected movable head was related to head rotation, with the remaining brain injury potential of the blow being related to the contact phenomena of the impact. [86][87][88][89] Although the biodynamics in these primate models were likely more similar to human concussion, such studies were limited to small group size. With regard to modern-day athletes and the biophysics of mTBI, data garnered through helmet accelerometer studies at the youth, high school, and college level have shown that athletes may experience a wide range of head impacts, as well as types of forces, and this research has also suggested that it may be more likely be that the cumulative number of head impacts best correlates with the potential for concussion occurrence or chronic effects.…”
Section: Chronic Behavioral Sequelae After Repetitive Mild Traumatic mentioning
confidence: 99%
“…52,70,71,85,89,107 Analyses of the data at that time led investigators to believe that approximately half of the potential for concussion during impact to the unprotected movable head was related to head rotation, with the remaining brain injury potential of the blow being related to the contact phenomena of the impact. 71 Although the biodynamics in these primate models were likely more similar to human concussion, such studies were limited to small group size.…”
Section: The Biophysics Of Head Impactmentioning
confidence: 99%
“…Head kinematics have therefore been used to predict TBI pathology in both human and animal models, design safety equipment, and assess the risk of brain injury (2)(3)(4). However, to our knowledge, there have only been a handful of large animal studies that have used sensors (5)(6)(7)(8)(9) and/or high-speed cameras [see Table 1; (8,10,11)] to directly measure the magnitude of head kinematics during acceleration models of injury. To date, no studies have evaluated the reproducibility of head kinematics, which, by definition (65,66), requires the exact same initial injury conditions to be repeated across multiple animals (i.e., methods reproducibility) and/or in separate experiments (i.e., results reproducibility).…”
Section: Introductionmentioning
confidence: 99%